RAM1 and RAM2 function and expression during Arbuscular Mycorrhizal Symbiosis and Aphanomyces euteiches colonization - Gobbato, Enrico (Landes Bioscience, 2013)
The establishment of the symbiotic interaction between plants and arbuscular mycorrhizal (AM) fungi requires a very tight molecular dialogue. Most of the known plant genes necessary for this process are also required for nodulation in legume plants and only very recently genes specifically required for AM symbiosis have been described. Among them we identified RAM (Reduced Arbuscular Mycorrhization)1 and RAM2, a GRAS transcription factor and a GPAT respectively, which are critical for the induction of hyphopodia formation in AM fungi. RAM2 function is also required for appressoria formation by the pathogen Phytophtora palmivora. Here we investigated the activity of RAM1 and RAM2 promoters during mycorrhization and the role of RAM1 and RAM2 during infection by the root pathogen Aphanomyces euteiches. pRAM1 is activated without cell type specificity before hyphopodia formation, while pRAM2 is specifically active in arbusculated cells providing evidence for a potential function of cutin momomers in the regulation of arbuscule formation. Furthermore, consistent with what we observed with Phytophtora, RAM2 but not RAM1 is required during Aphanomyces euteiches infection.